MENCEGAH PENGARUH NEGATIF CYBERCRIME PADA ANAK-ANAK DI YAYASAN AL- KAHFI KP. KAYURINGIN JAYA, KOTA BEKASI - Octo Iskandar (Abdi Bhara, 2023)
The phenomenon of bullying or abuse has oftenoccurred since long ago. Bullying is any form of oppression orviolence that is carried out intentionally by one person or groupof people who are stronger or more powerful towards anotherperson, with the aim of causing harm and is carried outcontinuously. Bullying cases are now divided into two groups,namely verbal bullying, in which the perpetrator makes physicalcontact with the victim, such as hitting, pushing, kicking anddamaging the victim's belongings. Then the second is nonverbal,this is done by condescending, ridiculing, spreadinggossip to threatening the victim. In this digital era, Indonesianpeople definitely use technology, even from a young age to theelderly. Seeing increasingly sophisticated technologicaldevelopments makes us sometimes unable to control themalicious comments from other people. Cyberbullying is an actof bullying carried out on social media, activities carried out byperpetrators such as giving hurtful words in the commentscolumn, spreading lies, and sending messages containing threats.This activity was carried out to provide early knowledge tochildren in the Kayuringin, South Bekasi, about the dangers ofcyberbullying.